Expression of fox-related genes in the skin follicles of Inner Mongolia cashmere goat - Han, Wenjing (Asian-Australasian journal of animal sciences, 2018)
OBJECTIVE: This study investigated the expression of genes in cashmere goats at different periods of their fetal development